PENGARUH IMPLEMENTASI KURIKULUM BERBASIS KKNI TERHADAP PENINGKATAN MUTU PENDIDIKAN PTAIN - Khairiah Khairiah (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
The purpose of this study was to determine the influence of KKNI based (Indonesian national qualifications framework) curriculum toward the improvement of the education quality of PTAIN (State collage for islamic studies). The method of discussion done  by the author  is the observation at IAIN Bengkulu, equipped by literature  study that packaged using descriptive qualitative analysis based on some opinions, Thought and reviews from experts in the field of education, academics and education practitioners who are competent. The result shows  that the implementation/ execution of KKNI through  several  stages  including  preparing the learning  achievements, formulating  a profile of graduates of study programs, formulating competency standards learning outcomes, formulating the achievement of learning courses, formulating  the achiement of course learning outcomes/CLO, finding key concepts and keywords to the  achievement of the  learning  courses, RPKPS development (planning programs and  learning  activities  of the semester): The quality improvement of PTKIN influenced by the implementation / application of KKNI based curriculum through  three  main  factors:  (1) the adequacy of educational resources in terms  of the quality of staff, cost and means of learning; (2) the quality of the learning process that encourages students to learn effectively and (3) the quality of output  in form of knowledge and attitude  skills. Then it can be recommended that PTKIN should immediately implement the curriculum of KKNI to improve the education quality of PTKIN